2006
DOI: 10.1139/f05-256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-head barriers on stream fishes: taxonomic affiliations and morphological correlates of sensitive species

Abstract: Low-head barriers used in the control of parasitic sea lamprey (Petromyzon marinus) in the basin of the Laurentian Great Lakes can alter the richness and composition of nontarget fishes in tributary streams. Identification of taxa sensitive to these barriers is an important step toward mitigating these effects. Upstream–downstream distributions of fishes in 24 pairs of barrier and reference streams from throughout the basin were estimated using electrofishing surveys. For 48 common species from 34 genera and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 42 publications
0
51
0
Order By: Relevance
“…A strong correlation exists between habitat variables and fish assemblages, which imply that fragmentation and modification of riverine habitat can have profound effects on biotic integrity (Dynesius and Nilsson, 1994;McLaughlin et al, 2006;Harford and McLaughlin, 2007). The protection and conservation, as well as restoration and management of running water environments, requires an exact knowledge of the ecological demands of the most important species in order to genuinely understand the influence of the habitat alterations at a local scale (Jungwirth et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation exists between habitat variables and fish assemblages, which imply that fragmentation and modification of riverine habitat can have profound effects on biotic integrity (Dynesius and Nilsson, 1994;McLaughlin et al, 2006;Harford and McLaughlin, 2007). The protection and conservation, as well as restoration and management of running water environments, requires an exact knowledge of the ecological demands of the most important species in order to genuinely understand the influence of the habitat alterations at a local scale (Jungwirth et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Helfrich et al (1999) discovered that fish species traits (e.g., swimming ability) appeared to be related to low-head dam passage, and they observed the cumulative effect of multiple low-head dams on fish assemblages. However, McLaughlin et al (2006) revealed that taxonomic affiliation and swimming morphology were not useful for predicting sensitivity to barriers for fishes, while Santucci et al (2005) did not find the obvious evidence of cumulative effects of multiple low-head dams. Cummings (2004) examined the influence of local habitat, network-specific measures and low-head dam on the fish species richness in headwater streams.…”
Section: Introductionmentioning
confidence: 93%
“…Although a great deal of attention has been given to analyzing the effects of individual barriers, especially on fish, (e.g., Jungwirth et al 1998;Peter 1998;McLaughlin et al 2006), 85 surprisingly little attention has been given to the cumulative effect of barriers at the scale of river drainage networkriver networks. Methods to measure effects of multiple barriers at the extent of the entire landscape are in their infancy considered ; (Beechie et al 1994;Wheeler et al 2005).…”
Section: Introductionmentioning
confidence: 99%